Solar cell sensitizer models [Ru(bpy-R)2(NCS)2] probed by spectroelectrochemistry - Kämper, Sara; Paretzki, Alexa; Fiedler, Jan; Záliš, Stanislav; Kaim, Wolfgang (Inorganic chemistry, 2012)
Complexes [Ru(bpy-R)(2)(NCS)(2)], where R = H (1), 4,4'-(CO(2)Et)(2) (2), 4,4'-(OMe)(2) (3), and 4,4'-Me(2) (4), were studied by spectroelectrochemistry in the UV-vis and IR regions and by in situ electron paramagnetic resonance (EPR). The experimental information obtained for the frontier orbitals as supported and ascertained by density functional theory (DFT) calculations for 1 is relevant for the productive excited state. In addition to the parent 1, the ester complex 2 was chosen for its relationship to the carboxylate species involved for binding to TiO(2) in solar cells; the donor-substituted 3 and 4 allowed for better access to oxidized forms. Reflecting the metal-to-ligand (Ru → bpy) charge-transfer characteristics of the compounds, the electrochemical and EPR results for compounds 1-4 agree with previous notions of one metal-centered oxidation and several (bpy-R) ligand-centered reductions. The first one-electron reduction produces extensive IR absorption, including intraligand transitions and broad ligand-to-ligand intervalence charge-transfer transitions between the one-electron-reduced and unreduced bpy-R ligands. The electron addition to one remote bpy-R ligand does not significantly affect the N-C stretching frequency of the Ru(II)NCS unit. Upon oxidation of Ru(II) to Ru(III), however, the single N-C stretching band exhibits a splitting and a shift to lower energies. The DFT calculations serve to reproduce and understand these effects; they also suggest significant spin density on S for the oxidized form.